(untitled) (Journal Of Educational and Psychological Researches, 2018)
The current research aims to know the method and strategy of rainstorming for students to open the door towards innovation and creativity in the field of teaching the subject of geography and the importance of brainstorming method and the studies that touched on it. The study also dealt with the steps of teaching the method of brainstorming and the most important (traditional and modern), and the difficulties of using the method of brainstorming in the teaching process, as well as explained the guidance to improve teaching using the method of brainstorming in the teaching process. In light of the current research, the researcher concludes: 1 - The teaching methods of modern and student-centered may give better results than other strategies, centered on the teacher or teacher or educational material. 2 - The strategy of brainstorming helps to improve student science, which increases the scientific achievement. 3 - The strategy of brainstorming helps to raise the interest of the student and works to stimulate his ideas and help him to innovate. 4 - The use of brainstorming strategy increases the student’s interest in creative ideas and innovation as "and quality" The main recommendations of the research are: 1- Adopting strategy or method of brainstorming in geography for all stages 2 - Training teachers and teachers to use this method in the teaching of social materials at all stages and even the university stage. 3 - The researcher recommends teachers, teachers and teachers to fluctuate modern ideas in the process of teaching and work to encourage and develop. The most important proposals were as follows: 1 - The application of this research, which includes strategy or method of brainstorming in the academic stages, especially social materials. 2 - Preparation of a similar study and applied to students in the academic stages in the field of geography especially to know the effect of using the method or strategy of brain storming in teaching.